Design, synthesis and biological evaluation of novel biphenylsulfonamide derivatives as selective AT2 receptor antagonists - Wang, Danhui; Zhao, Wenjie; Zhang, Zuzhi; Zhang, Yanchun; Li, Jiaming; Huang, Weijun (Frontiers in Chemistry, 2022)
A novel series of benzenesulfonamide derivatives that selectively act on AT2 receptor had been designed and synthesized. The binding affinity and functional activity were evaluated by radio-ligand binding analysis and cell neurite outgrowth assay with NG108-15 cells separately. The compounds 8d, 8h, 8i, 8j, 8l and 9h exhibited moderate selectivity and affinity for AT2 receptor. Among them, 8j exhibited agonist activity and 8l displayed similar selectivity to AT2 receptor with PD123,319. Molecular docking was carried out to analysis the binding mode and binding site between the compound and AT2 receptor to provide reference for further development.